FRI0230 Assessment of Safety, Pharmacokinetics and Pharmacodynamics of A Novel anti-CD40 Monoclonal antibody, CFZ533, in Healthy Volunteers and in Rheumatoid Arthritis Patients. (15th July 2016) - Slade, A.; Koo, P.; He, Y.; Espie, P.; Auger-Sarrazin, A.; Rush, J.; Gergely, P.
Abstract : Background: Aberrant CD40-CD154 pathway signaling has been linked to pathology in autoimmune disease. Blocking the CD40-CD154 pathway prevents T cell-dependent antibody responses, germinal center formation and prolongs renal allograft survival in non-human primates. CFZ533 is a novel, fully human, non-agonistic Fc-silent, anti-CD40 monoclonal antibody being developed for treatment of autoimmune diseases and prevention of rejection in solid-organ transplantation. Objectives: To assess the safety, pharmacokinetics (PK) and pharmacodynamics activity (PD) of CFZ533 in humans. Methods: A double-blind, placebo controlled, ascending, single-dose study was conducted in 48 healthy volunteers (HV) receiving 0.03, 0.1, 0.3, 1.0, 3.0 mg/kg i.v., 3.0 mg/kg s.c. CFZ533 or matching placebo (3:1) as well as in 12 rheumatoid arthritis (RA) patients receiving 10.0 mg/kg i.v. CFZ533 or placebo (1:1). HVs were immunized with a single intramuscular dose of a T-cell dependent neo-antigen, Keyhole Limpet Hemocyanin (KLH) with alum adjuvant on Day 3 and again between Day 29–85 depending on predicted loss of CD40 receptor occupancy (RO) as a function of CFZ533 dose. Blood samples for PK, CD40 RO and anti-KLH IgG and IgM profiling were collected at multiple time points during the study. Anti-KLH antibodies were assessed using a validated human ELISA system with an LOQ of 0.7 (IgG) and 2.1 (IgM) μg/mL. RA patients were evaluated for safety, PK and RO. Results: All doses of CFZ533 and KLH were safe and well tolerated. CFZ533 PK concentrations were quantifiable at all dose levels tested. Complete (≥90%) peripheral CD40 RO by 3 mg/kg i.v. CFZ533 in HVs was maintained for 28 days. During this period of full RO, full suppression of the primary humoral response to KLH was evident in all treated subjects (KLH administered 2 days after CFZ533 dosing). After complete CFZ533 washout in 3 mg/kg cohort, all subjects mounted a robust anti-KLH response following a re-challenge on Day 85. Full RO in RA patients who received 10 mg/kg i.v. CFZ533 was maintained for at least 6 weeks and up to 10 weeks. Conclusions: The favorable safety and tolerability profile of CFZ533 coupled with a predictable concentration-CD40 receptor occupancy relationship and suppression of a primary T cell-dependent antibody response supports future clinical trials of CFZ533 in select autoimmune diseases and transplantation. Disclosure of Interest: A. Slade Employee of: Novartis Pharmaceuticals Corporation, East Hanover, NJ, USA, P. Koo Employee of: Novartis Pharmaceuticals Corporation, East Hanover, NJ, USA, Y. He Employee of: Novartis Pharmaceuticals Corporation, Cambridge, MA, USA, P. Espie Employee of: Novartis Pharmaceuticals Corporation, Basel, Switzerland, A. Auger-Sarrazin Employee of: Novartis Pharmaceuticals Corporation, Basel, Switzerland, J. Rush Employee of: Novartis Pharmaceuticals Corporation, Basel, Switzerland, P. Gergely Employee of: Novartis Pharmaceuticals Corporation, Basel, Switzerland